2010
DOI: 10.4314/pamj.v5i1.56178
|View full text |Cite
|
Sign up to set email alerts
|

Regular vitamin C supplementation during pregnancy reduces hospitalization: outcomes of a Ugandan rural cohort study

Abstract: BACKGROUND: Vitamin C or ascorbic acid is a hydro-soluble lactone (synthesized from glucose) essential to human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…A higher quality diet during pregnancy was associated with lower diastolic blood pressure ( 34 ). Consumption of vitamin C supplements in a group of 384 pregnant women reduces the hospitalisation time even if there is no access to fruit and vegetables ( 37 ). Changamir et al conducted a study on 8468 pregnant women in 2015 and found that women who took multivitamins during pregnancy had better gestational weights, which is a significant predictor of birth weight ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…A higher quality diet during pregnancy was associated with lower diastolic blood pressure ( 34 ). Consumption of vitamin C supplements in a group of 384 pregnant women reduces the hospitalisation time even if there is no access to fruit and vegetables ( 37 ). Changamir et al conducted a study on 8468 pregnant women in 2015 and found that women who took multivitamins during pregnancy had better gestational weights, which is a significant predictor of birth weight ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The available information is based on animal data, some clinical studies and observations in adult patients. For example, maternal ascorbic acid overdosage can increase the risk of hyperoxaluria 28 . High dosing can also lead to nausea, abdominal pain and other gastrointestinal problems.…”
Section: Characteristics Of Ascorbic Acid Intake During Pregnancymentioning
confidence: 99%
“…Vitamin C, on the contrary, has potent antioxidant activity in hydrophilic environments, acting as a scavenger of reactive oxygen and nitrogen species. In addition, vitamin C plays a significant role in the regeneration of oxidized vitamin E (14).…”
Section: ' Introductionmentioning
confidence: 99%